Simulations of centriole of polarized centrosome as a monopole antenna in immune and viral synapses - Dvorak, Josef; Melichar, Bohuslav; Filipova, Alzbeta; Grimova, Jana; Grimova, Nela; Rozsypalova, Aneta; Buka, David; Voboril, Rene; Zapletal, Radek; Buchler, Tomas; Richter, Igor; Buka, David (Journal of B.U.ON., 2018)
The immune synapse (IS) is a temporary interface between an antigen-presenting cell and an effector lymphocyte. Viral synapse is a molecularly organized cellular junction that is structurally similar to the IS. Primary cilium is considered as a functional homologue of the IS due to the morphological and functional similarities in architecture between both micotubule structures. It has been hypothesized that endogenous electromagnetic field in the cell is generated by a unique cooperating system between mitochondria and microtubules. We are extending this prior hypothesis of the endogenous electromagnetic field in the cell postulating that polarized centriole in immune and viral synapse could serve as a monopole antenna. This is an addition to our hypothesis that primary cilium could serve as a monopole antenna. We simulated the distribution of electric field of centriole of polarized centrosome as a monopole antenna in immune and viral synapse. Very weak electromagnetic field of polarized centriole of CD8+ T lymphocyte in IS can contribute to the transport of cytolytic granules into the attacked (cancer) cell. Analogically, very weak electromagnetic field of polarized centriole in viral synapse of infected CD4 cells can aid the transport of viruses (human immunodeficiency virus) to non-infected CD4 cells. We hypothesized that healthy organisms need these monopole antennas. If, during the neoplastic transformation, healthy cells lose monopole antennas in form of primary cilia, the IS aims to replace them by monopole antennas of polarized centrioles in IS to restore homeostasis.
Keywords: imunitní systém; mikrotubuly; Immune System; centrioly; Neoplasms; nádory; synapse; centrozom; lidé; CD8-Positive T-Lymphocytes; Electromagnetic Fields; polarita buněk; CD8-pozitivní T-lymfocyty; Centrioles; Centrosome; elektromagnetická pole; Cell Polarity; Microtubules; Synapses; Humans